2020
DOI: 10.1093/nar/gkaa737
|View full text |Cite
|
Sign up to set email alerts
|

Base pairing, structural and functional insights into N4-methylcytidine (m4C) and N4,N4-dimethylcytidine (m42C) modified RNA

Abstract: The N4-methylation of cytidine (m4C and m42C) in RNA plays important roles in both bacterial and eukaryotic cells. In this work, we synthesized a series of m4C and m42C modified RNA oligonucleotides, conducted their base pairing and bioactivity studies, and solved three new crystal structures of the RNA duplexes containing these two modifications. Our thermostability and X-ray crystallography studies, together with the molecular dynamic simulation studies, demonstrated that m4C retains a regular C:G base pairi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…In one report of duplex RNAs containing m4C, there was a slight decrease in duplex stability when the modification was present. 108 This decrease in stability for G-m4C correlated with an observed increased ΔpK a compared to G−C. In contrast, other studies showed an opposite correlation between oligonucleotide stabilities and ΔpK a between donor and acceptor pairs.…”
Section: G G G Gmentioning
confidence: 84%
See 1 more Smart Citation
“…In one report of duplex RNAs containing m4C, there was a slight decrease in duplex stability when the modification was present. 108 This decrease in stability for G-m4C correlated with an observed increased ΔpK a compared to G−C. In contrast, other studies showed an opposite correlation between oligonucleotide stabilities and ΔpK a between donor and acceptor pairs.…”
Section: G G G Gmentioning
confidence: 84%
“…We used the Δp K a rule with adjusted theoretical p K a values and compared to published stability data. In one report of duplex RNAs containing m4C, there was a slight decrease in duplex stability when the modification was present . This decrease in stability for G-m4C correlated with an observed increased Δp K a compared to G–C.…”
Section: Resultsmentioning
confidence: 99%
“… ( a ) An example of how a modification can affect base-pairing interactions. Here, N 4 , N 4 -dimethylcytidine (in pink) has only two possible base-pairing sites on its W-C-F edge due to the double substitution of methyl groups on the amine, while a typical G: C base pair would have three [ 36 ]. ( b ) An example of three base pairs, one only with canonical bases, and the other with one RNA modification (5-methylcytidine, illustrated in pink).…”
Section: Figurementioning
confidence: 99%
“…As we know, the visualization of these “host–guest” interactions based on X-ray crystallography will help understand the details of interactions between functional intercalations and targets, as well as the nucleotide conformational polymorphism changes. Although some related researches have been reported by single-crystal XRD ( Monestier et al, 2017 ; Chu et al, 2019 ; Geng et al, 2019 ; Satange et al, 2019 ; Mao et al, 2020 ), the well-defined structure of “host–guest” interaction about intercalator-mismatched DNA remains as a fundamental and challenging issue for comprehensive understanding of the biological processes in genomic DNA. A proper design and synthesis of molecular building blocks is an effective methodological strategy to obtain innovative functional materials, which is an ultimate target in supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%